The Polygon of Progress in the Epoch of Retardation: Architecture of universities within the context of global stabilization - Lidin, Konstantin (project baikal, 2015)
In the 1970s the period of global development in the context of the hyperbolic growth of the key indicators came to its end. The demographic, economic, scientific and technical growth decelerated. Against the background of the reduced flow of innovations the social image of universities changes, while approaching the image of medieval monasteries. The architecture of universities evolves accordingly. It tends to isolate campuses from the city structure and aspires to international and supranational stylistics, which is common for universities of the whole world.